Strengthening Guidance and Counseling Management in Improving Student Well-Being and Quality of Educational Services - Ujam Jaenudin (Universitas Islam Nusantara, Bandung, 2024)
The acceleration of globalization and digitalization demands career readiness among students from the upper secondary level onwards. However, the gap between academic achievement and career maturity remains a significant challenge. This study employs a descriptive qualitative approach with a case study design at SMAN 1 Sindangkasisih and SMAN 1 Cihaurbeuti, Ciamis Regency. Data collection techniques include interviews, observations, and documentation, with thematic analysis and triangulation of sources and methods. Findings indicate that both schools have formal career guidance and counseling (BK) structures, but their implementation is not yet optimal. Major obstacles include limited BK teachers, conventional methods, minimal digital training, and low student participation. However, students actively participating in the program showed significant improvements in self-awareness, career assertiveness, and decision-making skills. Collaborative and adaptive BK management was proven effective in enhancing students' career readiness. Continuous training for BK teachers, technology integration, and strengthened institutional support are needed to ensure the program runs systematically and has a broad impact.